A Critical Discourse Analysis of the National Islam and Foreign Islam in the Australian Press - GHAURI, MUHAMMAD JUNAID; UMBER , SALMA (Islamic Studies, 2019)
Recent studies conducted in the UK, US, and Europe have highlighted the major differences regarding coverage of internal (i.e., National) Islam and external (i.e., Foreign) Islam, with foreign Islam covered and viewed as the greater threat. This paper explores the prominent themes of National Islam and Foreign Islam in the editorials of Australian newspapers in the period from January 1, 2016 to March 31, 2017. Employing Teun A. van Dijk’s (b. 1943) ideological square and lexicalisation approaches within the critical discourse analysis paradigm, this study examined editorials from two leading newspapers: “The Australian” and “The Age.” The findings show that both newspapers focused and highlighted conflict, violence, and collectivism regarding Islam and Muslims while covering Foreign Islam, with “The Australian” highlighting the underrepresentation of women as well. On the other hand, when discussing National Islam, “The Age” focused on victimisation and prejudice towards Muslims in Australia and emphasised the need for understanding, harmony, and cohesion. On the contrary, “The Australian” associated National Islam with the same themes associated with Foreign Islam i.e., violence, collectivism, conflict, and women underrepresentation.